Xác lập khung kĩ năng mềm cốt lõi cho sinh viên đại học - cơ sở khoa học cho xây dựng giáo trình - Lê Kim Liên , Lê Kim Liên (Tạp chí Giáo dục, 2026)
In the context of digital transformation and deep globalization, the labor market increasingly requires university graduates to possess not only disciplinary knowledge but also essential soft skills for adaptability, collaboration, and sustainable career development. The mismatch between soft skills training programs and business needs leads to a situation where many graduates are not ready for the workplace. This study aims to identify key soft skills for Vietnamese university students as a scientific basis for developing an integrated soft skills curriculum. A survey of 574 participants - including employers, experts, and students - was conducted using frameworks from OECD (2018), Trilling and Fadel (2009), and Robles (2012). Descriptive statistics and ANOVA analyses revealed four core skills with high consensus: collaboration, initiative, critical thinking, and adaptability/resilience. However, the ANOVA test indicates statistically significant differences (p < .05) in perceptions between students and the other two groups regarding both the importance and the degree of skill gaps. Students tend to underestimate the level of deficiency in key skills compared to the assessments of employers and experts, reflecting a gap between university education and the practical requirements of the labor market. The study recommends redesigning soft skills curricula through experiential and project- based learning, multi- source assessment, and stronger collaboration among universities, industry, and students to enhance graduates’ employability and global integration in the digital era.